2002
DOI: 10.1161/01.str.0000032302.91894.0f
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Tests After Intracerebral Hemorrhage in the Rat

Abstract: Background and Purpose-In humans, intracerebral hemorrhage (ICH) causes marked perihematomal edema formation and neurological deficits. A rat ICH model, involving infusion of autologous blood into the caudate, has been used extensively to study mechanisms of edema formation, but an examination of behavioral outcome would improve its preclinical utility and provide a more rigorous assessment of the pathological cascade of events over time. The purpose of this study was to use a battery of sensorimotor function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
335
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 456 publications
(341 citation statements)
references
References 42 publications
4
335
2
Order By: Relevance
“…13,19,33 The test is well suited for testing both mice and rats. It is one of the only tests that can detect mild injury and chronically stable deficits in mice.…”
Section: Corner Turn Testmentioning
confidence: 99%
“…13,19,33 The test is well suited for testing both mice and rats. It is one of the only tests that can detect mild injury and chronically stable deficits in mice.…”
Section: Corner Turn Testmentioning
confidence: 99%
“…This and our previous study [22] illustrate that the choice of behavioral tests depends on the model of stroke, the location and severity of insult, the timing of testing, as well as practical limitations [22]. For the whole blood model, we recommend using the single pellet-reaching task with other simple, less time-consuming tasks (e.g., forelimb placing score) known to be sensitive to long-term deficits in this insult [17]. We expect that such a battery will improve preclinical studies and help to identify truly effective therapies.…”
Section: Discussionmentioning
confidence: 93%
“…The infusion of blood, rather than collagenase, better mimics the single large bleed that occurs in most ICH patients [15]. Using this ICH model, Hua et al [17] carefully identified a battery of tests sensitive to injury, tracked recovery over time, and examined the relationship between functional outcome and brain edema. Although each of their tests (corner turn test, forelimb use asymmetry (cylinder) test and forelimb placing test) detected ICH injury, marked recovery to pre-surgical levels occurred by 1 month in two of the tests.…”
mentioning
confidence: 99%
“…The significant neurological impairment in our model has never been reported in pig model of ICH by others. Many neurologic impairment assessment methods had been described, including Zea Longa assessment of neurological deficits (Longa et al 1989), spontaneous ipsilateral circling test, contralateral hindlimb retracting test, beam walking test (Altumbabic et al 1998), forelimb placing test, forelimb asymmetry test, and corner turn test (Schallert et al 2000;Hua et al 2002), but whether these methods are suitable for piglet model of ICH remains unknown. After taking all these tests into consideration, we chose and modified Zea Longa's assessment, which was easily performed and could evaluate the accurate condition of neurological deficits of piglets.…”
Section: Discussionmentioning
confidence: 99%